2017
DOI: 10.4103/1450-1147.181151
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of standardized uptake value on 18fluorine-fluorodeoxyglucose positron emission tomography/computed tomography in patients with nasopharyngeal carcinoma

Abstract: The aim of this study was to investigate the prognostic significance of standardized uptake value (SUV) on 18 fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in patients with nasopharyngeal carcinoma (NPC). Thirty-four patients who have histologically proven NPC and underwent 18F-FDG PET/CT were included in this study. After 18F-FDG PET/CT, all the patients received radiation therapy and 32 of them received concomitant weekly chemotherapy. The maximum SUV (SUVmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…SUV value of more than 3 was considered significant as a reliable predictive value for predicting malignancy. This method of PET/CT SUVmax was selected as a relative minimum cut-off value for best optimal sensitivity and accuracy and was relied upon the average SUVmax results of the previous studies [14][15][16].…”
Section: Data Interpretation and Image Analysismentioning
confidence: 99%
“…SUV value of more than 3 was considered significant as a reliable predictive value for predicting malignancy. This method of PET/CT SUVmax was selected as a relative minimum cut-off value for best optimal sensitivity and accuracy and was relied upon the average SUVmax results of the previous studies [14][15][16].…”
Section: Data Interpretation and Image Analysismentioning
confidence: 99%
“…Furthermore, another monocentric study from Turkey investigated the role of primary tumor and lymph node SUV max on the outcome of 32 patients. The authors observed a statistical trend towards worse survival for patients with higher SUV max of the primary tumor [36]. Unfortunately, both Turkish studies did not include further volumetric PET parameters like MTV or TLG.…”
Section: Plos Onementioning
confidence: 96%
“…This could be due to the short follow-up period. Several studies suggest that N-SUV max is more important than T-SUV max for prediction of DMFS in NPC patients(Lin et al 2016)(Türkölmez et al 2017;Jeong et al 2017). In another study, Chen et al reported that a high N-SUV max on pretreatment [ 18 F] FDG PET/CT (> 7.75) was an independent prognostic factor for worse DMFS in NPC patients(Chen et al 2015).…”
mentioning
confidence: 99%
“…In another study, Chen et al reported that a high N-SUV max on pretreatment [ 18 F] FDG PET/CT (> 7.75) was an independent prognostic factor for worse DMFS in NPC patients(Chen et al 2015). Furthermore, Türkölmez et al demonstrated that high T-SUV max and N-SUV max were related to death risk(Türkölmez et al 2017). Similarly, our results reported that high N-SUV max (> 9.4) was signi cantly associated with poor OS and PFS, with HR of 0.7 (95% CI, 0.48-1.01; p = 0.05) and 0.52 (95% CI, 0.29-0.93; p = 0.02) for OS and PFS, respectively.…”
mentioning
confidence: 99%